Testing the veracity of claims of Lewis acid catalysis - Šolić, Ivan (2019)
Are reactions employing Lewis acids really catalysed by those Lewis acids, or by “hidden Brønsted acids”, i.e. Brønsted acids generated in situ by hydrolysis? Testing of a series of reactions using Sc(III), Fe(III), In(III) and Y(III) by addition of 2,6-di-t-butyl-4-methylpyridine reveal that all are likely to follow the latter pathway. A reaction claimed to be catalysed by CBr4 through halogen bonding is also likely to be Brønsted acid catalysed.